Sustentabilidade de Barra do Garças sob a Ótica do Índice de Desenvolvimento Sustentável para Municípios - Greyce Bernardes de Mello Rezende (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
A county is considered sustainable, as it avoids the degradation of environmental system, reduces social inequalities, offers its inhabitants one built healthy and safe environment as well as public policy and articulates citizenship actions that address the present and future challenges. Therefore, the most appropriate measures for local sustainability are related to public policies aiming at the integration of social, environmental, economic and institutional dimensions. In this perspective, this research developed a quantitative, exploratory and descriptive, aimed to verify the the degree of sustainability of Barra do Garças (MT), by applying the tool Index of Sustainable Development for Municipalities (ISDM). Regarding the results, the city has an ISDM of 0,5461, an index with acceptable performance as parameters used in the methodology. However, we note that this index is close to an alert condition, which demonstrates that public policies should be implemented to improve the quality of life of citizens